Analisis Perbandingan Kinerja Keuangan Sebelum Dan Setelah Masa Pandemi Covid-19 (Studi Kasus Pada Pemerintah Daerah Provinsi Kalimantan Barat) - Widasari, Rieke; Susilo Jahja, Adi (CV. Multi Kreasi Media, 2023)
The changes in the working system during the Covid-19 pandemic have had a significant impact on local governments. One of the areas affected is the financial performance of regional governments. In addressing the challenges posed by the Covid-19 pandemic, governments need budget implementation strategies to ensure the stability of financial performance. This research aims to analyze and compare the financial performance of West Kalimantan Province before and after the Covid-19 pandemic (from 2019 to 2022). The study employs a quantitative descriptive method by observing five financial performance indicators of local governments. The ratios used include the fiscal decentralization ratio, regional financial independence ratio, effectiveness ratio of local own-source revenues (PAD), efficiency ratio, harmony ratio, and growth ratio. The research results indicate that, overall, West Kalimantan Province has performed relatively well in terms of financial management. However, there are aspects of finance that experienced a significant decline during the Covid-19 pandemic.